Public Communication in The Era of The Communication and Information Technology Revolution - Fitri Hardianti; Fatmawati; Yuli Rahmi Pratiwi (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2022)
Government’s Riau through Diskominfotik Riau Province has adapted to using technology for public communication. The aim is to find out the description of public communication carried out by the Diskominfotik Riau Province in the era of the communication and information technology revolution. The method used is qualitative, data collection techniques namely observation, interviews and documentation. Data analysis technique used Miles and Huberman and technique validity of the data was using Triangulation. The results showed that public communication carried out by Diskominfotik Riau Province went through a number of stages. The first stage is collecting data from various sources. The next stage is data analysis and presenting it in a content which will be disseminated to the public. After the content is ready, then it is distributed to all media channels of Government’s Riau including the website mediacenter.riau.go.id, social media government’s Riau and don't forget to also broadcast on online radio.